Differences in total yield and physicochemical attributes of virgin coconut oil from coconut milk demulsification using direct heating and microwave heating - Wan Anwar Fahmi, Wan Mohamad; Nur Diyanna, Mohd Yusof (2019)
The objective of the present study is to determine the total yield and physicochemical properties of virgin coconut oil (VCO) extracted from coconut milk using controlled direct heating and microwave heating. The heating temperature for the controlled direct heating method was 90 ˚C for the first hour of heating and maintained at 60 ˚C once the oil began to separate from the coconut protein until the demulsification was over. In the microwave heating method, coconut milk was heated at medium microwave power level (500W) for 30 minutes at 5 minutes intervals. The heating process for both methods was stopped before the proteinaceous latik turned brown. The recovered oils were subjected to four standard analyses for accessing the quality of VCO, which are moisture content (MC), iodine value (IV), peroxide value (PV) and acid value (%FFA). The percentage of oil yield and time taken during heating process for the controlled direct heating and microwave heating methods showed significant differences where the highest oil recovery (23.83%) with the shortest time taken (15.33 minutes) was given by the microwave heating method. There were no significant differences in the physicochemical properties of VCO extracted from both heating methods. By comparing the quality of the experimental VCOs to a commercial VCO, the VCO extracted from the controlled direct heating and microwave heating methods had no significant differences (p >0.05) than the commercial VCO. The present obtained results would be useful for micro and small-scale enterprises to correctly apply the heating methods in producing a high quality VCO commercially.